Cuerpos desgarrados: textualidades desgarradoras. Una aproximación a la escritura de Claudia Hernández - Rodríguez Corrales, Carla (2014)
The contemporary American literary production constitutes a space for the subjects identity (des) configuration and the collapse of the cultural-imaginary speech. This premise requires search and constant re‐signifying. For this reason, the following work focuses on the study of the ‘cuentario’ De fronteras (2007) of the salvadoran writer Claudia Hernández. The reading of this proposal allows approaching to the body-subjects (des)construction types that live both the literary and cultural textualities and – as a counterpoint - enables the body-subjects (des) articulation of the imaginary and cultural texts. Therefore, we’ll talk about textual bodies, fragmented spellings, corporeal cracks that can become stressed when trying to ‘be’, ‘live’: ‘say’.